12.1 EVALUATION OF ACUTE EFFECTS OF COFFEE CONSUMPTION ON ARTERIAL STIFFNESS IN HEALTHY ADULT PEOPLE USING AN OSCILLOMETRIC DEVICE - Pedro Forcada; Dario Echeverry; Alejandro Pizano; Felix Montes; Daniel Acuña (Artery Research, 2016)
Environment/Objectives: Several studies in different populations and conditions shown contradictory results about the effect of coffee on arterial stiffness (AS). Coffee consumption is high around the world and it is very important to define its CV effects. To evaluate the acute effects on haemodynamic parameters and AS, after consumption of regular coffee or, decaffeinated coffee. Methods: In a prospective, self controlled cohort study we included 32 healthy p. (46.2±10.4y.o., 16 men (53.5±18) and 16 women (43.0±21)(p=0,186)). Fourteen regular coffee consumers (87.5%) (p=NS). Haemodynamic parameters and AS were assessed non invasively using oscilometric Arteriograph® (TensioMed Budapest, Hungary Ltd.). Each subject received 14 gr. of excelso coffee (151.2 mg caffeine) and two weeks apart, 14 gr of decaf coffee (3.92 mg) in random order. Baseline, 30 and 60 min parameters are reported. Results: SBP increased at 30 and 60 min 3.9 mmHg (p=0.013) y 3.8 mmHg (p=0.002) respectively, la DBP increased 4.1 mmHg (p=0.001) y 3.2 mmHg (p=0.003), MAP 4.0 mmHg (p<0.001) y 3.3 mmHg (p=0.001), Heart rate decreased 3.2 (p=0.002) and 5 latidos/minuto (p<0.001) and aortic SBP increased 5.8 mmHg (p=0.002) and 7.6 mmHg (p=0.003) only with caffeine. Brachial Aix increased 19.9% at 30 (p<0.001) and 20.0% at 60 minutes (p<0.001). Aortic Aix increased 10.05% (p<0.001) y 10.2% (p<0.001) only with caffeine. PWV was not affected by caffeine (p=0.861). The shift of these parameters was mainly driven by changes in women. Conclusions: Caffeine at usual doses (two expresos) increased peripheral AS but not aortic PWV, specially in women.